RELATIONSHIP OF INCENTIVES AND WORK ENVIRONMENT TO ORGANIZATIONAL COMMITMENTS IN EMPLOYEES OF PT. KB FINANSIA MULTI FINANCE - K. Seljuna Monika; Nenny Anggraini; Rajagukguk , Wilson (Universitas Kristen Indonesia, 2022)
This study aims to determine how the relationship between incentives and work environment to the organizational commitment of PT. KB Finansia Multi Finance. Which is a company engaged in financing, which is located at the Depok branch on Jl. IR. H. Juanda NO. 11 & 12 RT. 001/014 Ex. Kemiri Advance, Kec. Beji Depok. This research is descriptive quantitative. And this type of research is a case study with data collection through the provision of a list of questions (questionnaires), with a sample of 50 employees of PT. KB Finansia Multi Finance. Testing this hypothesis using the technique of sperm rank correlation analysis. Based on the results of this study indicate that, there is a significant relationship between incentives and organizational commitment as indicated by the value of tcount (5,707) > ttable (2,010). With this, the Spearman Rank correlation value is 0.636. There is a significant relationship between offering incentives and organizational commitment, as indicated by the value of tcount (6,714) > ttable (2,010). With this, the Spearman Rank correlation value is 0.696. there is a significant relationship between the work environment and organizational commitment. Companies should pay more attention to offering special incentives to give praise to employees, companies can better improve the work environment, especially pay attention to whether employees work together with colleagues so that employees are loyal and fully committed to an organization or company.Keywords: Incentives, Work Environment And Organizational Commitment.